Neuromuscular diseases in elderly - Perić Stojan; Basta Ivana (Medicinski Podmladak)
Introduction: Even though neuromuscular diseases are not the first association in the elderly, the results of previous epidemiological studies record an increase in the incidence of acquired immune-mediated neuropathies, amyotrophic lateral sclerosis (ALS), myasthenia gravis (MG), inflammatory myopathies (IM) and inclusion body myositis (IBM). Bearing that in mind, this study aims to review neuromuscular diseases in people over 65 years of age. Discussion: In the population of elderly people, there is a significant increase in the incidence of ALS, with the peak of the disease between the ages of 70 and 80. Myasthenia gravis (MG) represents a heterogeneous group of diseases whose common features is weakness and excessive fatigue of skeletal muscles during prolonged or repeated activity. It is known to have two peaks. The first peak is recorded between the ages of 20 and 29, with more frequent disease in women, while the second peak is registered between the ages of 60 and 69 with a more frequent occurrence of the disease in men. Regarding acquired polyneuropathies CIDP and dysimmune polyneuropathies show a significant incidence in the geriatric population. Inflammatory myopathies such as polymyositis and dermatomyositis are of particular importance because they most often occur in patients over 65 years of age. Conclusion: Although neuromuscular diseases are not the first association when considering the differential diagnosis of neurological diseases in elderly patients, it can still be said that this group of diseases is often present in the geriatric population. The importance of early recognition of neuromuscular diseases in elderly patients is great, bearing in mind that most of them are curable neurological diseases. Timely diagnosis and early initiation of adequate treatment is a prerequisite for a favorable course and outcome of the disease in these patients.